The Lay knowledge regarding the prevention of complications related to childbirth: Perceptions of Congolese pregnant women - Claudine Tshiama; Gédéon Bongo; Oscar Nsutier; Mukandu Basua Babintu (Qualitative Research in Medicine & Healthcare, 2022)
During pregnancy, women sometimes choose certain practices based upon the experience of their family and/or their vicinity to anticipate complications that may occur during childbirth. The main objective of this study is to understand the motivations and perceptions of pregnant women on lay knowledge in the prevention of complications related to childbirth among a sample of Congolese women. We conducted this study at N’djili Referral Hospital in Kinshasa, Democratic Republic of Congo, using a qualitative phenomenological survey and indepth face-to-face interviews. We interviewed seven women on the phenomenon of lay knowledge practice in the prevention of maternal difficulties and analyzed the data using thematic coding. We provided a consent form to the participants and were careful not to include identifying information. Three main themes emerged: i) discussion of complications related to pregnancy and delivery, ii) perceptions about lay knowledge in preventing complications related to childbirth, and iii) suggestions from participants about using lay knowledge in healthcare settings. Based upon data collected, we argue that lay knowledge about pregnancy can be integrated into formal antenatal training when appropriate and, in doing so, we can build trust among pregnant women toward professional medical instruction.